2012
DOI: 10.1007/s10067-012-2112-3
|View full text |Cite
|
Sign up to set email alerts
|

The effect of dry needling in the treatment of myofascial pain syndrome: a randomized double-blinded placebo-controlled trial

Abstract: The objective of this study was to test the hypothesis that dry needling is more effective than sham dry needling in the treatment of myofascial pain syndrome (MPS). This was a prospective, double-blinded, randomized-controlled study conducted in an outpatient clinic. Thirty-nine subjects with established myofascial trigger points were randomized into two groups: study group (N = 22) and placebo group (N = 17). Dry needling was applied using acupuncture needles, and sham dry needling was applied in the placebo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
122
1
7

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(132 citation statements)
references
References 22 publications
2
122
1
7
Order By: Relevance
“…In a study by Tekin et al the immediate effects of DDN on pain and quality of life was compared with that of sham dry needling in 39 patients and DDN was found superior to sham dry needling. [9] Likewise Itoh et al observed that DDN is more effective than traditional acupuncture and superficial dry needling, for pain relief and neck disability in 40 patients and these effects lasted for 12 weeks. [8] On the other hand Hsieh et al used 25 G hypodermic needles for dry needling (peppering technique) in 14 MPS patients, and peppering was found effective for reducing pain and improving range of motion immediateley after the procedure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study by Tekin et al the immediate effects of DDN on pain and quality of life was compared with that of sham dry needling in 39 patients and DDN was found superior to sham dry needling. [9] Likewise Itoh et al observed that DDN is more effective than traditional acupuncture and superficial dry needling, for pain relief and neck disability in 40 patients and these effects lasted for 12 weeks. [8] On the other hand Hsieh et al used 25 G hypodermic needles for dry needling (peppering technique) in 14 MPS patients, and peppering was found effective for reducing pain and improving range of motion immediateley after the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…There are a number of studies in the literature demonstrating its efficacy. [7][8][9] The other technique that uses hypodermic needles is first described by Travell and Simons in 1942 on the other hand.…”
Section: Introductionmentioning
confidence: 99%
“…The results of this research has shown that dry needling, with manipulation -needle insertion and needle stimulation -or without -needle insertion alone -may or not 10.21611/qirt.2016.118 be beneficial in pain reduction [7][8][9][10]. The differences across protocols, enrolled patients, outcome selection and measurement techniques do not allow to formulate a definite position on the efficacy of the technique in trigger point rehabilitation.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have addressed the effects of dry needling application in patients with myofascial trigger points with inconclusive results but few have investigated its application in latent myofascial trigger points [7][8][9][10]. Regardless of the number of studies, the methodological variability makes it difficult to conclude on the effectiveness of dry needling, specially in latent myofascial trigger points.…”
Section: Introductionmentioning
confidence: 99%
“…2 Research is emerging supporting the use of TrP-DN for conditions such as back and neck pain, [11][12][13] shoulder pain, 14 and upper quadrant myofascial pain. 15 Furlan et al 16 conducted a systematic Cochrane meta-review of randomized controlled trials investigating acupuncture and TrP-DN for back pain. Trigger point dry needling was found to be a useful adjunct to other therapies in the treatment of persons with chronic low back pain.…”
Section: Introductionmentioning
confidence: 99%